Unveiling the potential of silicon carbide as a support material and membranes for oily wastewater remediation - Romero, Arthur S.; Innocentini, Murilo D.M.; Vladimir Oliveira, J.; Lider, Andrey; Fey, Tobias; Travitzky, Nahum; Hotza, Dachamir (Separation and Purification Technology, 2025)
The increasing global water consumption, especially due to industrial growth, results in a proportional generation of wastewater that must be treated before reuse or return to nature. Effective solutions are especially needed for treating oily wastewater, a common industrial effluent with serious environmental and public health consequences when discharged untreated. Membrane separation processes have emerged as a promising technology to replace conventional methods for oil–water separation due to their selectivity and environmental benefits. While polymeric membranes currently dominate industrial oily wastewater treatment, challenges such as fouling susceptibility and poor stability against chemicals hinder their long-term sustainability. In response, highly hydrophilic ceramic membranes, especially silicon carbide (SiC), have gained significant attention owing to their remarkable attributes, including high durability, chemical resistance, and mechanical stability. SiC membranes enable the treatment of oil solutions with high concentrations, bypassing the need for additional pre-treatment steps. Notably, SiC membrane separation is considered an environmentally friendly method for reducing oil, dissolved organic matter, and salt in the crude oil–water-rich phase, enhancing the industrial viability of oily wastewater separation in various processes, including wastewater treatment plants, petroleum, food, and pharmaceuticals. This review article provides a comprehensive overview of the state-of-the-art in SiC membranes for efficient oily wastewater treatment, encompassing processing methods, membrane properties, and performance evaluation. Moreover, it delves into the challenges and future directions of SiC membranes, including fouling mitigation, cost-effectiveness, and scalability. By shedding light on the untapped potential of SiC membranes, this review aims to contribute to the advancement of sustainable oily wastewater treatment technologies.
CRIS-Team Scopus Importer:2024-08-09
Keywords: Membrane separation processes; Oily wastewater treatment; Silicon carbide